STRATEGY FOR STRENGTHENING THE REGIONAL ECONOMIC RESILIENCE OF NORTH SUMATERA PROVINCE THROUGH SUSTAINABLE ECONOMIC TRANSFORMATION - Zulkarnain Nasution; Henky Japina (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of Regional Economic Innovation and Green Economy on Regional Economic Resilience with Digital Governance as a moderation variable in 33 districts/cities in North Sumatra Province for the 2020–2025 period. The study uses an explanatory quantitative approach with secondary data in the form of panel data which is analyzed using panel data regression through Common Effect Model, Fixed Effect Model, and Random Effect Model. The selection of the best model was carried out using the Chow Test, Hausman Test, and Lagrange Multiplier Test, while hypothesis testing was carried out through t-test, F test, determination coefficient, and Moderated Regression Analysis (MRA). The results of the study show that the Fixed Effect Model is the best model. Regional Economic Innovation, Green Economy, and Digital Governance have a positive and significant effect on Regional Economic Resilience. In addition, Digital Governance has been proven to strengthen the influence of Regional Economic Innovation and Green Economy on Regional Economic Resilience. The Adjusted R² value of 81.8% indicates that the model has an excellent ability to explain variations in regional economic resilience. These findings affirm the importance of strengthening regional innovation, implementing a green economy, and accelerating the transformation of digital government as a sustainable, adaptive, inclusive, and competitive regional economic development strategy in North Sumatra Province.